Dynamic linkages among transparency, income inequality and economic growth in developing countries: evidence from panel vector autoregressive (PVAR) model - Chia, Poh San; Law, Siong Hook; Trinugroho, Irwan; Wiwoho, Jamal; Damayanti, Sylviana Maya; Sergi, Bruno S. (Elsevier, 2022)
This study examines the dynamic linkage among transparency, financial development, income inequality and economic growth of 68 developing countries from 2000 to 2016, using a Panel Vector Autoregressive (PVAR) model. Two transparency indicators namely: (i) World Governance Indicators (WGI) and (ii) Global Index of Information Transparency and Accountability (GIITA). The empirical results indicate that transparency index from WGI is positively significant determinant of economic growth, while the GIITA transparency index is positive but insignificant. Both transparency indicators, however, have no effect on income inequality. In terms of Granger causality, there is a uni-directional causal effect running from transparency to economic growth. The analysis also incorporated financial development in the model and this variable is positive and significant Granger causes economic growth but not income inequality. The variance decomposition and impulse response functions results are consistent with the panel causality results.